Modern trends in philosophy of medicine - Mardiyeva, Ziyoda Alisherovna; Majidov, Sherzod Farxodovich (Science and Education, 2023)
The paper deals with the issues of the place and significance of philosophy in medicine as a methodological basis for scientific knowledge, the art of rational assumption, the relationship between philosophy and medicine, the unification of philosophical and medical knowledge, and the need to overcome professional limitations with a focus on the socio-philosophical understanding of their medical practice.